Colonial vestiges, difficult heritage, and the post-colony: Rescuing Ian Smith's collections at the Gwenoro ecomuseum, Shurugwi - Simbarashe Shadreck Chitima (Routledge, 2022)
This chapter engages with the politics of remembering and forgetting in the post-colonial context and explores how the concept of an ecomuseum offers possibilities of traversing complex histories and painful narratives. The chapter focusses on the proposed Gwenoro ecomuseum which will be located at a farm that once belonged to Ian Douglas Smith (1919–2007), the last Prime Minister of Rhodesia (1963–1980). Following his death, part of this farm was given to Midlands State University (MSU). Heritage experts at the university immediately saw the historical value of this ranch and subsequently secured Ian Smith’s personal belongings to establish an ecomuseum. The chapter explores how heritage professionals are navigating their way around a potentially sensitive collection of a very controversial figure. They should strike a balance between glorifying colonial figures and providing the narrative of the former colonised. The preservation of Ian Smith’s collections must not be misconstrued as a celebration of his legacy and colonial dominance. The chapter highlights the politics of curating colonial heritage in the post-colony and the future of the Gwenoro ecomuseum project.